Jute (Corchorus olitorius var. O-72) stem lignin: variation in content with age (Bangladesh Journal of Botany, 2015)
Stem lignin content of a mature jute plant was found to be around 29% giving a deposition rate of 0.21% per day. The study was made on individual plants of different ages starting from five weeks when they were big enough to produce sufficient dry mass for lignin estimation to 16 weeks of age when a jute plant is ready for retting. An intense rate of increase (1.15%) was found during the 7th week of growth, probably due to a rise in temperature. Present data and the average rate of increase of lignin production can be considered as a reference value for projects working on producing low-lignin - jute varieties. DOI: http://dx.doi.org/10.3329/bjb.v43i3.21603 Bangladesh J. Bot. 43(3): 309-314, 2014 (December)